The Role of Brand Image, Brand Equity and Product Quality toward Customers' Attitudes to Consume Eco Friendly Cosmetic Product (An Empirical Study: Millennial Generation Female Customers in Indonesia) - Ayu Febriyanti Puspitasari (Department of Management, Faculty of Economics and Business, Brawijaya University, 2020)
This research is motivated by the increasingly competitive cosmetics product industry with an environmentally friendly concept in Indonesia. The phenomenon shows that there has been a change in consumption patterns in female Customers, especially cosmetic products from conventional cosmetics to environmentally friendly cosmetics. The purpose of this study was to determine the extent of the role of brand image, brand equity and product quality on the attitudes of female Customers of the millennial generation in Indonesia on the use of cosmetics with eco-friendly concepts, both partially and simultaneously. The population in this study is female Customers in Indonesia using stratified random sampling so that only female Customers are included in the millennial generation (ages 25-40 years) as the sample in this study. The results showed that brand image (and product quality) had a partially positive effect on costumer attitudes on the use of environmentally friendly cosmetic products. Brand Equity does not show a positive relationship to consumer attitudes because customers are more impressed by the brand image and quality of environmentally friendly cosmetic products. Brand image brand equity product quality also have a positive role simultaneously on consumer attitude on the use of environmentally friendly cosmetic products. This research highlight the response of millennial female Customers who are very adaptive to the changing times in using environmentally friendly cosmetic products therefore it is recommended that environmentally friendly cosmetic manufacturers continue to innovate on existing products based on this strategies.